Method for improving seed crystal bonding quality

By performing polydopamine surface modification and low-temperature curing cross-linking on the graphite bottom stent, and using a heating disk with gradient thermal conductivity, the defects caused by the violent reaction of adhesive molecules in the existing silicon carbide seed bonding process are solved, and the quality of silicon carbide single crystals is significantly improved.

CN119710904APending Publication Date: 2025-03-28JIANGSU TANKEBLUE SEMICON CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411950898.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the existing silicon carbide seed bonding process, high curing temperature leads to violent reaction of the adhesive molecules, resulting in holes and bubbles, affecting the quality of the silicon carbide single crystal.

Method used

By modifying the graphite bottom stent with polydopamine surface, the surface activity and flatness are increased, and curing and cross-linking is carried out under low temperature conditions to reduce defects inside the glue layer. At the same time, a heating plate with a gradient thermal conductivity is used to ensure uniform curing of the glue layer.

Benefits of technology

It improves the bonding reliability between the seed crystal and the bottom bracket, reduces the appearance of bubbles and holes, and improves the quality of silicon carbide single crystal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005214847260000011
    Figure HDA0005214847260000011
  • Figure HDA0005214847260000012
    Figure HDA0005214847260000012
  • Figure HDA0005214847260000021
    Figure HDA0005214847260000021
Patent Text Reader

Abstract

The invention provides a method for improving seed crystal bonding quality. A dopamine polymer layer is formed on the surface of the graphite bottom support by utilizing a dopamine modified graphite bottom support and utilizing a surface grafting technology, so that the surface activity and flatness of the graphite bottom support are improved, the binding force between the bottom support and an adhesive layer is increased, in addition, low-temperature curing and crosslinking are utilized, the curing and crosslinking reaction time is prolonged, the reaction intensity is reduced, and the service life of the adhesive layer is prolonged. The defects of bubbles, holes and the like in the adhesive layer are reduced. Meanwhile, the heat-conducting disc with gradient heat conductivity coefficient is adopted, the adhesive layer in the central area is firstly cured and crosslinked, the adhesive layer at the edge part is not cured at the moment, bubbles can be orderly discharged from the center to the edge, the phenomenon that the bubbles in the central area cannot be discharged and are gathered is avoided, and finally, the bonding quality of the seed crystal and the graphite bottom support is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicon carbide, and in particular relates to a method for improving the bonding quality of seed crystals. Background Art

[0002] Silicon carbide single crystals are generally prepared by physical vapor transport. The preparation method is usually to place silicon carbide powder at the bottom of a graphite crucible, and then bond the silicon carbide seed crystal to the graphite tray at the top of the graphite crucible. The silicon carbide powder is heated by induction heating or resistance heating to make it sublime. Under the action of the temperature gradient, the gas phase silicon carbide is transported to the top of the graphite crucible and grows on the silicon carbide seed crystal to become a silicon carbide single crystal. Among them, the bonding process of the silicon carbide seed crystal is first to apply the adhesive on the silicon carbide seed crystal, and then bond the silicon carbide seed crystal to the graphite paper, and then apply the adhesive on the graphite tray, and then bond the graphite tray to the graphite paper with the silicon carbide seed crystal. After the bonding is completed, the adhesive needs to be heated and pressurized to cure and cross-link the adhesive to increase the bonding strength. The curing temperature used in the general process is relatively high (over 150°C). At this temperature, the curing and cross-linking reaction of the adhesive molecules is violent, which easily produces large holes, bubbles and other defects. The bubbles are large and numerous, the adhesive layer is extremely unevenly distributed, and the exposed area on the back of the silicon carbide seed crystal is large. Heat will gather at the bubbles, which leads to the back of the silicon carbide seed crystal being prone to sublimation or even burn-through during the growth of the silicon carbide single crystal, making the grown silicon carbide single crystal ingot have defects such as polycrystalline, polymorphic, microtubules, and dislocations, which seriously affect the quality of the silicon carbide crystal. In addition, during hot pressing curing, the thermal conductive material is uniform, and the curing time of the glue in the center and the edge is relatively small, which easily leads to the inability to discharge the bubbles in the center, and the large bubbles gather in the center area of ​​the seed crystal, which seriously affects the quality of the subsequent crystal growth. Therefore, how to improve the reliability of the bonding between the seed crystal and the base, so that the two are closely connected, reduce bubbles, and improve the bonding quality is a technical problem that needs to be solved urgently. Summary of the invention

[0003] In view of this, the technical problem to be solved by the present invention is to provide a method for improving the bonding quality of the seed crystal. The method provided by the present invention can ensure the reliability of the bonding between the seed crystal and the base, and improve the bonding quality of the seed crystal.

[0004] The present invention provides a method for improving the bonding quality of a seed crystal, comprising the following steps:

[0005] A) performing surface modification of the graphite base with polydopamine to obtain a modified graphite base;

[0006] B) coating a resin adhesive on the surface of the modified graphite base to obtain a graphite base coated with the resin adhesive;

[0007] C) coating the surface of the seed crystal with resin glue and then pasting graphite paper on it to obtain a seed crystal pasted with graphite paper;

[0008] D) pasting the seed crystal pasted with graphite paper on the surface of the graphite base coated with resin glue to obtain the graphite base pasted with the seed crystal;

[0009] E) placing the graphite base with the seed crystal attached thereto on the surface of a heating plate and heating the plate in stages while applying pressure to the surface of the seed crystal to complete the attachment of the seed crystal; the heating plate is a heating plate with a gradient thermal conductivity, and the thermal conductivity of the heating plate gradually decreases from the center to the outside.

[0010] Preferably, in step A), the method for surface modification of polydopamine comprises the following steps:

[0011] A1) preparing a buffer solution, adding dopamine hydrochloride and ammonium persulfate to the buffer solution to obtain a dopamine solution;

[0012] A2) placing the graphite base in a dopamine solution to undergo a self-polymerization reaction to obtain a modified graphite base.

[0013] Preferably, the buffer solution is selected from disodium hydrogen phosphate-citric acid buffer solution;

[0014] In the dopamine solution, the concentration of dopamine hydrochloride is 1 to 5 mg / mL, and the concentration of ammonium persulfate is 1 to 3 mg / mL;

[0015] The self-polymerization reaction time is 2 to 10 hours.

[0016] Preferably, in step B) and step C), the resin glue is epoxy resin glue.

[0017] Preferably, the heating plate is composed of a central heat-conducting layer, a first heat-conducting ring arranged at the periphery of the central heat-conducting layer, and a second heat-conducting ring arranged at the periphery of the first heat-conducting ring, from the center to the outside.

[0018] The thermal conductivity of the central heat-conducting layer>the thermal conductivity of the first heat-conducting ring>the thermal conductivity of the second heat-conducting ring.

[0019] Preferably, the thermal conductivity of the central heat-conducting layer is 200 to 500 W / (m·K);

[0020] The thermal conductivity of the first heat-conducting ring is 100-200 W / (m·K);

[0021] The thermal conductivity of the second heat-conducting ring is 30-100 W / (m·K).

[0022] Preferably, the central heat-conducting layer, the first heat-conducting ring and the second heat-conducting ring have the same thickness and a flatness less than 10 μm.

[0023] Preferably, the pressure is applied by applying a weight on the surface of the seed crystal, and the mass of the weight is 5 to 300 kg.

[0024] Preferably, the heating during the process is carried out in an inert gas atmosphere.

[0025] Preferably, the stage heating includes:

[0026] Raise the temperature to 60-200°C at 5-20°C / min and keep warm for 30-60min;

[0027] Then increase the temperature to 400°C at 5-20°C / min and stop heating.

[0028] Compared with the prior art, the present invention provides a method for improving the bonding quality of seed crystals, comprising the following steps: A) performing surface modification of a graphite base with polydopamine to obtain a modified graphite base; B) coating a resin adhesive on the surface of the modified graphite base to obtain a graphite base coated with the resin adhesive; C) pasting graphite paper after coating the resin adhesive on the surface of the seed crystal to obtain a seed crystal pasted with graphite paper; D) pasting the seed crystal pasted with graphite paper on the surface of the graphite base coated with the resin adhesive to obtain a graphite base pasted with the seed crystal; E) placing the graphite base pasted with the seed crystal on the surface of a heating plate and performing staged heating while applying pressure on the surface of the seed crystal to complete the pasting of the seed crystal; the heating plate is a heating plate with a gradient thermal conductivity, and the thermal conductivity of the heating plate gradually decreases from the center to the outside. The present invention utilizes dopamine to modify the graphite base, and utilizes the technology of surface grafting to form a dopamine polymer layer on the surface of the graphite base, thereby increasing the surface activity and flatness of the graphite base, thereby increasing the bonding force between the base and the adhesive layer. In addition, low-temperature curing and cross-linking are utilized to increase the curing and cross-linking reaction time, reduce the intensity of the reaction, and reduce defects such as bubbles and holes inside the adhesive layer. At the same time, a heat-conducting disc with a gradient thermal conductivity is used, and the adhesive layer in the central area is first cured and cross-linked, while the adhesive layer in the edge part is not cured, and the bubbles can be discharged in an orderly manner from the center to the edge, thereby avoiding the phenomenon that the bubbles in the central area cannot be discharged and gather, and finally ensuring the bonding quality between the seed crystal and the graphite base. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of the structure of the heating plate provided by the present invention;

[0030] Figure 2 A schematic diagram of the structure of the device for bonding seed crystals provided by the present invention;

[0031] Figure 3 This is a back photo of the ingot prepared in Comparative Example 1;

[0032] Figure 4This is a back photo of the ingot prepared in Comparative Example 2;

[0033] Figure 5 This is a back photo of the ingot prepared in Comparative Example 3;

[0034] Figure 6 This is a back photo of the ingot prepared in Example 1;

[0035] Figure 7 This is a photo of the back of the ingot prepared in Example 2. DETAILED DESCRIPTION

[0036] The present invention provides a method for improving the bonding quality of a seed crystal, comprising the following steps:

[0037] A) performing surface modification of the graphite base with polydopamine to obtain a modified graphite base;

[0038] B) coating a resin adhesive on the surface of the modified graphite base to obtain a graphite base coated with the resin adhesive;

[0039] C) coating the surface of the seed crystal with resin glue and then pasting graphite paper on it to obtain a seed crystal pasted with graphite paper;

[0040] D) pasting the seed crystal pasted with graphite paper on the surface of the graphite base coated with resin glue to obtain the graphite base pasted with the seed crystal;

[0041] E) placing the graphite base with the seed crystal attached thereto on the surface of a heating plate and heating the plate in stages while applying pressure to the surface of the seed crystal to complete the attachment of the seed crystal; the heating plate is a heating plate with a gradient thermal conductivity, and the thermal conductivity of the heating plate gradually decreases from the center to the outside.

[0042] The present invention first modifies the graphite base, and forms a dopamine polymer layer on the surface of the graphite base by using the surface grafting technology, thereby increasing the surface activity and flatness of the graphite base, thereby increasing the bonding force between the graphite base and the adhesive layer.

[0043] Specifically, the method for surface modification of polydopamine comprises the following steps:

[0044] A1) preparing a buffer solution, adding dopamine hydrochloride and ammonium persulfate to the buffer solution to obtain a dopamine solution;

[0045] A2) placing the graphite base in a dopamine solution to undergo a self-polymerization reaction to obtain a modified graphite base.

[0046] Wherein, the buffer solution is selected from disodium hydrogen phosphate-citric acid buffer solution;

[0047] In the dopamine solution, the concentration of dopamine hydrochloride is 1 to 5 mg / mL, which can be 1, 2, 3, 4, 5, or any value between 1 and 5 mg / mL; the concentration of ammonium persulfate is 1 to 3 mg / mL, which can be 1, 1.5, 2, 2.5, 3, or any value between 1 and 3 mg / mL.

[0048] After the dopamine solution is prepared, the graphite base is placed in the dopamine solution for self-polymerization reaction. The self-polymerization reaction time is 2 to 10 hours, which can be 2, 3, 4, 5, 6, 7, 8, 9, 10, or any value between 2 and 10 hours.

[0049] Next, a resin adhesive is coated on the surface of the modified graphite base to obtain a graphite base coated with the resin adhesive, wherein the resin adhesive is preferably an epoxy resin adhesive.

[0050] After coating the surface of the seed crystal with resin glue, the graphite paper is pasted on it to obtain the seed crystal pasted with graphite paper, wherein the resin glue is preferably epoxy resin glue.

[0051] The present invention has no particular limitation on the order of step B) and step C).

[0052] The seed crystal pasted with graphite paper is pasted on the surface of the graphite base coated with resin glue to obtain the graphite base pasted with seed crystal, and finally a structure of seed crystal / resin glue layer / graphite paper / resin glue layer / polydopamine layer / graphite base is formed.

[0053] The graphite base with the seed crystal attached thereto is placed on the surface of the heating plate and the temperature is increased in stages while applying pressure to the surface of the seed crystal to complete the attachment of the seed crystal.

[0054] The heating plate has a gradient thermal conductivity, and the thermal conductivity of the heating plate gradually decreases from the center to the outside. By utilizing heat-conducting layers with different thermal conductivities and performing hot pressing in different regions, bubbles can be discharged in an orderly manner from the center to the edge when the glue is solidified, thereby avoiding the phenomenon that bubbles in the central region cannot be discharged and gather. The uniformity of the glue of the seed crystal prepared by the method of the present invention is greatly improved.

[0055] In some specific embodiments of the present invention, the heating plate is composed of a central heat-conducting layer, a first heat-conducting ring disposed on the periphery of the central heat-conducting layer, and a second heat-conducting ring disposed on the periphery of the first heat-conducting ring, from the center to the outside.

[0056] Wherein, the thermal conductivity of the central heat-conducting layer is greater than the thermal conductivity of the first heat-conducting ring and greater than the thermal conductivity of the second heat-conducting ring.

[0057] Preferably, the thermal conductivity of the central heat-conducting layer is 200 to 500 W / (m·K), and can be 200, 250, 300, 350, 400, 450, 500, or any value between 200 and 500 W / (m·K);

[0058] The thermal conductivity of the first heat-conducting ring is 100-200 W / (m·K), and can be 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, or any value between 100 and 200 W / (m·K);

[0059] The thermal conductivity of the second heat-conducting ring is 30-100 W / (m·K), and can be 30, 40, 50, 60, 70, 80, 90, 100, or any value between 30 and 100 W / (m·K).

[0060] In the present invention, there is no special restriction on the materials of the central heat-conducting layer, the first heat-conducting ring, and the second heat-conducting ring, as long as the thermal conductivity coefficients decrease in sequence. However, it should be noted that no matter what material is used, the thickness of the central heat-conducting layer, the first heat-conducting ring, and the second heat-conducting ring are the same, and the flatness is less than 10μm to ensure the bonding effect of the seed crystal.

[0061] In some preferred embodiments of the present invention, the central heat-conducting layer is circular, and the first heat-conducting ring and the second heat-conducting ring are circular rings, wherein the ratio of the circular radius of the central heat-conducting layer to the ring width of the first heat-conducting ring and the second heat-conducting ring is 2:1:1.

[0062] See also Figure 1 , Figure 1 The schematic diagram of the structure of the heating plate provided by the present invention is shown in FIG. 31 is a central heat-conducting layer, 32 is a first heat-conducting ring, and 33 is a second heat-conducting ring.

[0063] After placing the graphite base with the seed crystal attached thereto on the surface of the heating plate, the temperature is increased in stages while applying pressure on the surface of the seed crystal to complete the attachment of the seed crystal.

[0064] The pressure is applied by applying a weight on the surface of the seed crystal, and the mass of the weight is 5 to 300 kg, and can be 5, 10, 50, 100, 150, 200, 250, 300, or any value between 5 and 300 kg.

[0065] While the pressure is applied, the temperature is increased in stages in an inert gas atmosphere.

[0066] Wherein, the stage heating includes:

[0067] The temperature is increased to 60-200°C at a rate of 5-20°C / min and kept warm for 30-60min; wherein the heating rate can be 5, 10, 15, 20, or any value between 5-20°C / min, the heating temperature is 60, 80, 100, 120, 140, 150, 160, 180, 200, or any value between 60-200°C, and the keeping time is 30, 40, 50, 60, or any value between 30-60min.

[0068] Then the temperature is raised to 400°C at a rate of 5-20°C / min, and the heating is stopped. The heating rate may be 5, 10, 15, 20, or any value between 5-20°C / min.

[0069] In the present invention, the heating plate is placed on the surface of the heating platform.

[0070] Wherein, the structure for bonding the seed crystal is shown in Figure 2 , Figure 2 The schematic diagram of the structure of the device for bonding seed crystals provided by the present invention includes: 1-pressure weight, 2-graphite base with seed crystals attached, 3-heating plate, and 4-heating platform.

[0071] During the hot pressing process, the heating plate 3 is placed above the heating platform 4, and the central heat conducting layer 31 ( Figure 1 A first heating ring 32 is placed on the periphery of the central heat conducting layer 31 ( Figure 1 A second heating ring 33 is placed on the periphery of the first heating ring 32 ( Figure 1 The graphite base 2 with seed crystal attached thereto is placed on the heating plate 3, and then the pressure weight 1 is placed on the graphite base 2 with seed crystal attached thereto. The graphite base 2 with seed crystal attached thereto has one side of the seed crystal in contact with the pressure weight, and one side of the graphite base in contact with the heating plate 3.

[0072] In the present invention, the resin glue molecules will release a large amount of heat during the curing and cross-linking. If a higher temperature is provided to the resin glue molecules at this time, the curing and cross-linking reaction of the resin glue will be too intense, and defects such as bubbles and holes will be easily generated. The present invention cures and cross-links the adhesive at a temperature 10 to 20°C lower than the curing temperature of the resin glue, prolongs the reaction time, reduces defects such as bubbles and holes in the adhesive layer, and at the same time enhances the adhesion of the adhesive.

[0073] The present invention utilizes a dopamine-modified base, low-temperature curing cross-linking and a heat-conducting disk with a gradient thermal conductivity coefficient, so that the bonding quality between the graphite base and the seed crystal is improved, and defects such as back corrosion, impurity crystals and ablation during the crystal growth process are reduced.

[0074] In order to further understand the present invention, the method for improving the seed crystal bonding quality provided by the present invention is described below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0075] In the present invention, the epoxy resin glue is purchased from Shanghai Resin Factory Co., Ltd.;

[0076] Comparative Example 1

[0077] (1) Dilute the viscosity of the epoxy resin adhesive to 30 mPa·s with ethanol.

[0078] (2) Use a glue spreader to spin-coat the diluted epoxy resin glue on the surface of the seed crystal, and stick graphite paper on the surface of the seed crystal.

[0079] (3) Apply epoxy resin glue on the surface of the graphite base.

[0080] (4) The seed crystal of step 2 is bonded to the surface of the base of step 3.

[0081] (5) Place the base of step 4 in a hot press furnace with a weight of 140 kg to provide bonding pressure. In an inert gas atmosphere, heat to 200°C at 20°C / min, keep warm for 30 min, heat to 400°C at 10°C / min, stop heating, and take out when the temperature drops below 200°C.

[0082] (6) The back side photo of the SiC ingot grown from the seed crystal is shown in Figure 3 As shown, the crystal has a lot of back corrosion and the bonding quality is poor.

[0083] Comparative Example 2

[0084] (1) Dilute the viscosity of the epoxy resin adhesive to 30 mPa·s with ethanol.

[0085] (2) Use a glue spreader to spin-coat the diluted epoxy resin glue on the surface of the seed crystal, and stick graphite paper on the surface of the seed crystal.

[0086] (3) Apply epoxy resin glue on the surface of the graphite base.

[0087] (4) The seed crystal of step 2 is bonded to the surface of the base of step 3.

[0088] (5) Place the base of step 4 in a hot press furnace with a weight of 140 kg to provide bonding pressure. In an inert gas atmosphere, heat to 80°C at 15°C / min, keep warm for 50 min, heat to 400°C at 10°C / min, stop heating, and take out when the temperature drops below 200°C.

[0089] (6) The back side photo of the SiC ingot grown from the seed crystal is shown in Figure 4As shown, the crystal has moderate back corrosion and the bonding quality is poor.

[0090] Comparative Example 3

[0091] (1) Dilute the viscosity of the epoxy resin adhesive to 30 mPa·s with ethanol.

[0092] (2) Use a glue spreader to spin-coat the diluted epoxy resin glue on the surface of the seed crystal, and stick graphite paper on the surface of the seed crystal.

[0093] (3) Apply epoxy resin glue on the surface of the graphite base.

[0094] (4) The seed crystal of step 2 is bonded to the surface of the base of step 3.

[0095] (5) Place the base of step 4 in a hot pressing furnace. The heating plate has a gradient thermal conductivity. The thermal conductivity gradually decreases from the center to the outside. The heating plate is composed of a central thermal conductive layer, a first thermal conductive ring disposed on the periphery of the central thermal conductive layer, and a second thermal conductive ring disposed on the periphery of the first thermal conductive ring. The thermal conductivity of the central thermal conductive layer is 350W / (m·K); the thermal conductivity of the first thermal conductive ring is 150W / (m·K); and the thermal conductivity of the second thermal conductive ring is 50W / (m·K). The thickness of the central thermal conductive layer, the first thermal conductive ring, and the second thermal conductive ring are the same, and the flatness is less than 10μm. The central thermal conductive layer is circular, and the first thermal conductive ring and the second thermal conductive ring are circular rings, wherein the ratio of the circular radius of the central thermal conductive layer to the ring width of the first thermal conductive ring and the second thermal conductive ring is 2:1:1.

[0096] The mass of the added weight is 140 kg to provide bonding pressure. In an inert gas atmosphere, the temperature is raised to 180°C at 10°C / min, kept warm for 30 minutes, and then raised to 400°C at 10°C / min. Heating is stopped and the sample is taken out when the temperature drops below 200°C.

[0097] (6) The back side photo of the SiC ingot grown from the seed crystal is shown in Figure 5 As shown, the crystal has moderate back corrosion and the bonding quality is poor.

[0098] Comparative Example 4

[0099] (1) Dilute the viscosity of the epoxy resin adhesive to 30 mPa·s with ethanol.

[0100] (2) Use a glue spreader to spin-coat the diluted epoxy resin glue on the surface of the seed crystal, and stick graphite paper on the surface of the seed crystal.

[0101] (3) Apply epoxy resin glue on the surface of the graphite base.

[0102] (4) The seed crystal of step 2 is bonded to the surface of the base of step 3.

[0103] (5) Place the base of step 4 in a hot pressing furnace. The heating plate has a gradient thermal conductivity. The thermal conductivity gradually decreases from the center to the outside. The heating plate is composed of a central thermal conductive layer, a first thermal conductive ring disposed on the periphery of the central thermal conductive layer, and a second thermal conductive ring disposed on the periphery of the first thermal conductive ring. The thermal conductivity of the central thermal conductive layer is 350W / (m·K); the thermal conductivity of the first thermal conductive ring is 150W / (m·K); and the thermal conductivity of the second thermal conductive ring is 50W / (m·K). The thickness of the central thermal conductive layer, the first thermal conductive ring, and the second thermal conductive ring are the same, and the flatness is less than 10μm. The central thermal conductive layer is circular, and the first thermal conductive ring and the second thermal conductive ring are circular rings, wherein the ratio of the circular radius of the central thermal conductive layer to the ring width of the first thermal conductive ring and the second thermal conductive ring is 2:1:1.

[0104] The mass of the added weight is 140 kg to provide bonding pressure. In an inert gas atmosphere, the temperature is raised to 80°C at 10°C / min, kept warm for 50 minutes, and then raised to 400°C at 10°C / min. Heating is stopped and the sample is taken out when the temperature drops below 200°C.

[0105] (6) The crystals grown from this seed crystal have moderate back rot and poor bonding quality.

[0106] Comparative Example 5

[0107] (1) Prepare a sodium hydrogen phosphate-citric acid buffer solution with a pH of 7, add dopamine hydrochloride and ammonium persulfate to the buffer solution, wherein the concentration of dopamine hydrochloride is 2 mg / mL and the concentration of ammonium persulfate is 1.2 mg / mL, and place the base in the above solution for 5 hours.

[0108] (2) Dilute the viscosity of the epoxy resin adhesive to 30 mPa·s with ethanol.

[0109] (3) Use a glue spreader to spin-coat the diluted epoxy resin glue on the surface of the seed crystal, and stick graphite paper on the surface of the seed crystal.

[0110] (4) Apply epoxy resin glue on the surface of the graphite base modified in step 1.

[0111] (5) The seed crystal in step 3 is bonded to the surface of the base in step 4.

[0112] (6) Place the base of step 5 in a hot press furnace with a weight of 140 kg to provide bonding pressure. In an inert gas atmosphere, heat to 200°C at 15°C / min, keep warm for 30 min, heat to 400°C at 10°C / min, stop heating, and take out when the temperature drops below 200°C.

[0113] (7) The crystals grown from this seed crystal have moderate back rot and poor bonding quality.

[0114] Example 1

[0115] (1) Prepare a sodium hydrogen phosphate-citric acid buffer solution with a pH of 7, add dopamine hydrochloride and ammonium persulfate to the buffer solution, wherein the concentration of dopamine hydrochloride is 2 mg / mL and the concentration of ammonium persulfate is 1.2 mg / mL, and place the base in the above solution for 5 hours.

[0116] (2) Dilute the viscosity of the epoxy resin adhesive to 30 mPa·s with ethanol.

[0117] (3) Use a glue spreader to spin-coat the diluted epoxy resin glue on the surface of the seed crystal, and stick graphite paper on the surface of the seed crystal.

[0118] (4) Apply epoxy resin glue on the surface of the graphite base modified in step 1.

[0119] (5) The seed crystal in step 3 is bonded to the surface of the base in step 4.

[0120] (6) Place the base of step 5 in a hot pressing furnace. The heating plate has a gradient thermal conductivity. The thermal conductivity gradually decreases from the center to the outside. The heating plate is composed of a central thermal conductive layer, a first thermal conductive ring arranged on the periphery of the central thermal conductive layer, and a second thermal conductive ring arranged on the periphery of the first thermal conductive ring. The thermal conductivity of the central thermal conductive layer is 350W / (m·K); the thermal conductivity of the first thermal conductive ring is 150W / (m·K); and the thermal conductivity of the second thermal conductive ring is 50W / (m·K). The thickness of the central thermal conductive layer, the first thermal conductive ring, and the second thermal conductive ring are the same, and the flatness is less than 10μm. The central thermal conductive layer is circular, and the first thermal conductive ring and the second thermal conductive ring are circular rings, wherein the ratio of the circular radius of the central thermal conductive layer to the ring width of the first thermal conductive ring and the second thermal conductive ring is 2:2:1.

[0121] The mass of the added weight is 140kg to provide bonding pressure. In an inert gas atmosphere, the temperature is raised to 180℃ at 10℃ / min, kept warm for 30min, and then raised to 400℃ at 10℃ / min. Heating is stopped and the sample is taken out when the temperature drops below 200℃.

[0122] (7) The back side photo of the SiC ingot grown from the seed crystal is shown in Figure 6 As shown, the crystal has a small amount of back corrosion and the bonding quality is good.

[0123] Example 2

[0124] (1) Prepare a sodium hydrogen phosphate-citric acid buffer solution with a pH of 7, add dopamine hydrochloride and ammonium persulfate to the buffer solution, wherein the concentration of dopamine hydrochloride is 2 mg / mL and the concentration of ammonium persulfate is 1.2 mg / mL, and place the base in the above solution for 5 hours.

[0125] (2) Dilute the viscosity of the epoxy resin adhesive to 30 mPa·s with ethanol.

[0126] (3) Use a glue spreader to spin-coat the diluted epoxy resin glue on the surface of the seed crystal, and stick graphite paper on the surface of the seed crystal.

[0127] (4) Apply epoxy resin glue on the surface of the graphite base modified in step 1.

[0128] (5) The seed crystal in step 3 is bonded to the surface of the base in step 4.

[0129] (6) Place the base of step 5 in a hot pressing furnace. The heating plate has a gradient thermal conductivity. The thermal conductivity gradually decreases from the center to the outside. The heating plate is composed of a central thermal conductive layer, a first thermal conductive ring arranged on the periphery of the central thermal conductive layer, and a second thermal conductive ring arranged on the periphery of the first thermal conductive ring. The thermal conductivity of the central thermal conductive layer is 350W / (m·K); the thermal conductivity of the first thermal conductive ring is 150W / (m·K); and the thermal conductivity of the second thermal conductive ring is 50W / (m·K). The thickness of the central thermal conductive layer, the first thermal conductive ring, and the second thermal conductive ring are the same, and the flatness is less than 10μm. The central thermal conductive layer is circular, and the first thermal conductive ring and the second thermal conductive ring are circular rings, wherein the ratio of the circular radius of the central thermal conductive layer to the first thermal conductive ring and the second thermal conductive ring is 2:1:1.

[0130] The mass of the added weight is 140 kg to provide bonding pressure. In an inert gas atmosphere, the temperature is raised to 80°C at 10°C / min, kept warm for 50 minutes, and then raised to 400°C at 10°C / min. Heating is stopped and the sample is taken out when the temperature drops below 200°C.

[0131] (7) The back side photo of the SiC ingot grown from the seed crystal is shown in Figure 7 As shown, the crystal has very little back corrosion and the bonding quality is good.

[0132] Example 3

[0133] (1) Prepare a sodium hydrogen phosphate-citric acid buffer solution with a pH of 7, add dopamine hydrochloride and ammonium persulfate to the buffer solution, wherein the concentration of dopamine hydrochloride is 3 mg / mL and the concentration of ammonium persulfate is 2 mg / mL, and place the base in the solution for 7 hours.

[0134] (2) Dilute the viscosity of the epoxy resin adhesive to 30 mPa·s with ethanol.

[0135] (3) Use a glue spreader to spin-coat the diluted epoxy resin glue on the surface of the seed crystal, and stick graphite paper on the surface of the seed crystal.

[0136] (4) Apply epoxy resin glue on the surface of the graphite base modified in step 1.

[0137] (5) The seed crystal in step 3 is bonded to the surface of the base in step 4.

[0138] (6) Place the base of step 5 in a hot pressing furnace. The heating plate has a gradient thermal conductivity. The thermal conductivity gradually decreases from the center to the outside. The heating plate is composed of a central thermal conductive layer, a first thermal conductive ring disposed on the periphery of the central thermal conductive layer, and a second thermal conductive ring disposed on the periphery of the first thermal conductive ring. The thermal conductivity of the central thermal conductive layer is 400W / (m·K); the thermal conductivity of the first thermal conductive ring is 180W / (m·K); and the thermal conductivity of the second thermal conductive ring is 80W / (m·K). The thickness of the central thermal conductive layer, the first thermal conductive ring, and the second thermal conductive ring are the same, and the flatness is less than 10μm. The central thermal conductive layer is circular, and the first thermal conductive ring and the second thermal conductive ring are circular rings, wherein the ratio of the circular radius of the central thermal conductive layer to the first thermal conductive ring and the second thermal conductive ring is 2:1:1.

[0139] The mass of the added weight is 150 kg to provide bonding pressure. In an inert gas atmosphere, the temperature is raised to 90°C at 10°C / min, kept warm for 40 minutes, and then raised to 400°C at 10°C / min. Heating is stopped and the sample is taken out when the temperature drops below 200°C.

[0140] (7) There is a small amount of back corrosion in the SiC crystal grown from the seed crystal, and the bonding quality is good.

[0141] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for improving the bonding quality of a seed crystal, characterized in that: The following steps are involved: A) performing surface modification of the graphite base with polydopamine to obtain a modified graphite base; B) coating a resin adhesive on the surface of the modified graphite base to obtain a graphite base coated with the resin adhesive; C) coating the surface of the seed crystal with resin glue and then pasting graphite paper on it to obtain a seed crystal pasted with graphite paper; D) pasting the seed crystal pasted with graphite paper on the surface of the graphite base coated with resin glue to obtain the graphite base pasted with the seed crystal; E) placing the graphite base with the seed crystal attached thereto on the surface of a heating plate and heating the plate in stages while applying pressure to the surface of the seed crystal to complete the attachment of the seed crystal; the heating plate is a heating plate with a gradient thermal conductivity, and the thermal conductivity of the heating plate gradually decreases from the center to the outside.

2. The method according to claim 1, characterized in that In step A), the method for surface modification of polydopamine comprises the following steps: A1) preparing a buffer solution, adding dopamine hydrochloride and ammonium persulfate to the buffer solution to obtain a dopamine solution; A2) placing the graphite base in a dopamine solution to undergo a self-polymerization reaction to obtain a modified graphite base.

3. The method according to claim 2, characterized in that The buffer solution is selected from disodium hydrogen phosphate-citric acid buffer solution; In the dopamine solution, the concentration of dopamine hydrochloride is 1 to 5 mg / mL, and the concentration of ammonium persulfate is 1 to 3 mg / mL; The self-polymerization reaction time is 2 to 10 hours.

4. The method according to claim 1, characterized in that: In step B) and step C), the resin glue is epoxy resin glue.

5. The method according to claim 1, characterized in that The heating plate is composed of a central heat-conducting layer, a first heat-conducting ring arranged on the periphery of the central heat-conducting layer, and a second heat-conducting ring arranged on the periphery of the first heat-conducting ring, from the center to the outside. The thermal conductivity of the central heat-conducting layer>the thermal conductivity of the first heat-conducting ring>the thermal conductivity of the second heat-conducting ring.

6. The method according to claim 5, characterized in that The thermal conductivity of the central heat-conducting layer is 200 to 500 W / (m·K); The thermal conductivity of the first heat-conducting ring is 100-200 W / (m·K); The thermal conductivity of the second heat-conducting ring is 30-100 W / (m·K).

7. The method according to claim 5, characterized in that The central heat-conducting layer, the first heat-conducting ring and the second heat-conducting ring have the same thickness and a flatness less than 10 μm.

8. The method according to claim 1, characterized in that The pressure is applied by applying a weight on the surface of the seed crystal, and the mass of the weight is 5 to 300 kg.

9. The method according to claim 1, characterized in that: The temperature increase during the process is carried out in an inert gas atmosphere.

10. The method according to claim 1, characterized in that The stage heating includes: Raise the temperature to 60-200°C at 5-20°C / min and keep warm for 30-60min; Then increase the temperature to 400°C at 5-20°C / min and stop heating.

Citation Information

Cited By

  • Auxiliary seed crystal sticking heating element, seed crystal sticking heating element set, heating method and application

    CN120625186A

  • Flexible hot-pressing bonding device and method for 8-12-inch silicon carbide seed crystals

    CN122279761A